Review of Alternative Ranking Methods in Multi-Criteria Decision Analysis Based on WASPAS and CoCoSo Methodologies - Mukherjee, Asesh Kumar; Gazi, Kamal Hossain; Raisa, Nishat; Momena, Alaa Fouad; mukherjee, Shashi Bajaj; Sobczak, Anna; Salahshour, Soheil; Mondal, Sankar Prasad; Ghosh, Arijit (Yugoslav Journal of Operations Research, 2025)
Along with crisp data, one of the most popular methods in decision-making under uncertainty is the multi-criteria decision-making (MCDM) method. Over time, the MCDM process has incorporated numerous decision-making methods. Among these methods, WeightedAggregatedSumProductAssessment(WASPAS)andCombinedCompromise Solution (CoCoSo) are lauded for their effectiveness in handling complex, uncertain decision situations. Using these methods, numerous researchers have discussed in their research papers how to solve various problems observed in different areas of real life. Based on multiple previous research findings, this review paper provides a thorough description of the above MCDM methods. It explains in detail their theoretical basis, mathematical framework, computational methods, pseudocode, their use in various realworld problems, etc. in uncertain environments. A comparative discussion between the two methods is given which focuses on the similarities, contrasts, strengths, and weaknesses between them. Further, two real-world applications of these two methods were added and results were discussed in a comparative manner. Additionally, this review discusses the applicability of these methods in real-world decision-making contexts and identifies avenues for future research in this dynamic field.